Evidentiary Status of Crown Witnesses in Indonesia’s Anti-Corruption Proceedings: Legal Challenges and Human Rights Implications - Dwi Noviani Putri; Sumaidi; Nur Fauzia; Abdul Qadir Jaelani (CV. Dyoqu Publishing and Management, 2025)
Background: In corruption trials in Indonesia, the reliance on crown witnesses is widely debated. Their testimony may fill evidentiary gaps, yet the lack of explicit rules in KUHAP raises serious concerns about fairness and the protection of defendants’ rights. Aims: This paper examines how crown witnesses are positioned as evidence in anti-corruption proceedings, explores the legal complexities of their use, and considers the broader consequences for fair trial principles and human rights. Methods: Using a normative juridical approach, the study reviews KUHAP, the Anti-Corruption Law (Law No. 31/1999), and selected court cases. It also draws on academic literature and expert opinions to provide comparative insights into judicial practice. Result: The findings suggest that crown witness testimony, once given under oath, formally carries the same weight as ordinary witnesses. However, credibility issues persist, particularly when corroborating evidence is lacking, which risks undermining the presumption of innocence and creating conflicts among co-defendants. Courts often admit such testimony to address evidentiary shortages, but this practice places justice and human rights in delicate balance. Conclusion: While crown witness testimony can strengthen corruption cases, its unregulated use threatens fair trial guarantees. Clear legislative guidance is urgently needed to safeguard due process, harmonize practice with international human rights norms, and reinforce public confidence.